2012
DOI: 10.1142/s0192415x12500085
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Effects of a Hypoglycemic Fraction fromCucurbita ficifoliaBouché in Streptozotocin-Induced Diabetes Mice

Abstract: Type 2 diabetes is characterized by oxidative stress and a chronic low-grade inflammatory state, which also play roles in the pathogenesis of this disease and the accompanying vascular complications by increasing the production of free radicals and pro-inflammatory cytokines. Cucurbita ficifolia Bouché (C. ficifolia) is an edible Mexican plant whose hypoglycemic activity has been demonstrated in several experimental and clinical conditions. Recently, D-chiro-inositol has been proposed as the compound r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
3
14
0
7
Order By: Relevance
“…Treatment with C. ficifolia extract increased IL‐6 secretion, unlike treatment with DCI. Consistent with our results, in diabetic mice this extract increases the serum levels of IL‐6 . We propose that the increase in IL‐6 levels may have an effect on lipid metabolism similar to that reported with chito‐oligosaccharide.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Treatment with C. ficifolia extract increased IL‐6 secretion, unlike treatment with DCI. Consistent with our results, in diabetic mice this extract increases the serum levels of IL‐6 . We propose that the increase in IL‐6 levels may have an effect on lipid metabolism similar to that reported with chito‐oligosaccharide.…”
Section: Discussionsupporting
confidence: 92%
“…The fruit juice prepared from this plant has a hypoglycaemic effect in animals with experimental diabetes and in T2D patients . We recently demonstrated that the aqueous C. ficifolia extract has antioxidant and anti‐inflammatory effects, in addition to a glucose‐lowering effect, in streptozotocin‐induced diabetic mice . Apparently, the hypoglycaemic effect is due to the extract's content of D‐chiro‐inositol (DCI), which is part of the structure of inositol phosphoglycans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant action of C. ficifolia has been partially evaluated by general markers of oxidative stress, including, increased amounts thiobarbituric acid-reactive substances (TBARS) derived of lipid peroxidation, and GSH depletion. In this context, C. ficifolia reduces lipid peroxidation in pancreas of rats with streptozotocin-induced diabetes (Xia and Wang, 2007), also, a partial purified fraction of C. ficifolia (aqueous precipitate fraction) increase reduced glutathione (GSH) and decrease TBARS in liver and hearth of diabetic mice (Roman-Ramos et al, 2012). However, the mechanism involved in its antioxidant action and its effect on glutathione metabolism, and redox state, has not been completely studied.…”
Section: Introductionmentioning
confidence: 99%
“…[101] An extract of C. ficifolia, and synthetic D-chiro-inositol, both reduced oxidative stress as measured by changes in the ratio of oxidized to reduced glutathione in murine adipocytes: D-chiro-inositol, but not the plant extract, demonstrated insulin mimetic action. [102] Pumpkin seeds contain several molecules, including D-chiro-inositol, reported to have anti-glycemic effects and the seeds help maintain glycemic control. [103] Insulin prevents damage caused by the synaptic accumulation of amyloid β oligomers and this effect is enhanced by the presence of D-chiro-inositol.…”
Section: D-chiro-inositol Diabetes Pregnancy and Polycystic Ovary Smentioning
confidence: 99%